The Response of Picea abies Somatic Embryos to UV-B Radiation Depends on the Phase of Maturation - Eliášová, Kateřina; Vondráková, Zuzana; Gemperlová, Lenka; Neděla, Vilém; Runštuk, Jiří; Fischerová, Lucie; Malbeck, Jiří; Trávníčková, Alena; Cvikrová, Milena; Vágner, Martin (Frontiers in Plant Science, 2018)
UV-B radiation is a key environmental signal which initiates diverse responses that affect the metabolism, development, and viability of plants. In keeping with our previous studies, we concentrated primarily on how UV-B radiation affects Norway spruce (Picea abies (L.) Karst.) somatic embryo maturation and how phenolics and polyamines are linked to the defence response invoked by UV-B irradiation. We treated clusters of Norway spruce embryogenic culture (EC) with UV-B during the five stages of embryo maturation (early embryos, cylindrical and precotyledonary embryos, cotyledonary and mature embryos). For the first time we take an advantage of the unique environmental scanning electron microscope AQUASEM II to characterise somatic embryos in their native state. The severity of the irradiation effect on embryonal cell viability was shown to be dependent on the intensity of radiation as well as the stage of embryo development, and might also be related to differentiation of the outermost cell layers and formation of protoderm. The reduced ability of early embryos to activate the defence response, defined by an increase in malondialdehyde, a marked decrease in polyamine contents and a decline in phenolics, seems to be responsible not only for the severe cell damage and decrease in viability, but also for the inhibition of embryo development. The significant reduction in spermidine, which has been reported to be crucial for the somatic embryo development of several coniferous species, may be causally linked to the limited development of embryos. The pronounced decrease in cell wall-bound ferulic acid might correspond to failure of somatic embryos to reach more advanced stages of development. Embryos at later stages of development showed stress defence responses that were more efficient against UV-B exposure.